aFGF gene-modified adipose-derived mesenchymal stem cells promote healing of full-thickness skin defects in diabetic rats - Yiren Zhu; Pinhua Chen; Zhengchao Zhang; XueYi He; Ruoli Wang; Qi Fang; Zhixian Xu; Wubing He (Stem Cell Research & Therapy)
Abstract Background Chronic diabetic wounds pose a significant clinical challenge due to the limited efficacy of current treatments. This study aimed to investigate the role and potential mechanisms of adipose-derived mesenchymal stem cells (ADSCs) overexpressing acidic fibroblast growth factor (aFGF) in diabetic wound healing in a rat model. Methods ADSCs were genetically modified to achieve stable overexpression of aFGF. Varying doses of aFGF-ADSCs (1 × 106, 2 × 106, 3 × 106, 4 × 106) were injected into the muscular tissue surrounding diabetic rat wounds. We assessed aFGF expression and its impact on various stages of wound healing, including angiogenesis, inflammatory response, epithelialization, and collagen deposition. Transcriptomic sequencing was performed to explore the underlying mechanisms driving enhanced wound healing. Results Lentiviral transduction successfully induced stable aFGF overexpression in ADSCs. In vivo experiments revealed that varying doses of aFGF-ADSCs markedly enhanced wound healing in diabetic rats in a dose-dependent manner. The dose of 3 × 10⁶ aFGF-ADSCs demonstrated the most significant effect. In the 3 × 106 aFGF-ADSCs group, expression levels of aFGF, CD31, and CD163 were significantly higher than in other groups (p < 0.05), while CD86 expression was significantly lower (p < 0.05). Conclusion Single doses of aFGF-ADSCs comprehensively improved various aspects of wound repair in diabetic rats, offering a potential new approach for treating chronic diabetic wounds. The mechanism of action involves promoting angiogenesis, modulating inflammatory responses, accelerating epithelialization, and optimizing collagen deposition.